An analytical method for the thermo-mechanics coupling study of thin-walled spherical shell structure. Issue 13 (28th September 2022) - Zhu, Xingji; Jiang, Kainian; Liu, Qingchen; Tang, Lin; Xu, Longjun; Zhao, Guochen; Gong, Changqing
Abstract: For large LNG storage tanks, the thermal load has a very important influence on the failure mode of the thin-walled spherical dome. However, the traditional calculation of thermal stress is very complicated for the spherical shell. To obtain an analytic solution with a simple expression, an approximate method was proposed in this paper. The mechanical behaviour caused by the temperature difference is divided into two parts, i.e. the thermal strain directly acting on the shell and the binding force exerted by the boundary. The thickness is ignored in the calculation of deflection caused by boundary constraints. Then, its accuracy was verified by a linear elastic numerical model. Furthermore, the crack pattern in a nonlinear plastic simulation was also well captured. The case study shows that the thermal-induced meridional cracks distribute uniformly along the circumferential direction; these cracks first appeared on the inner surface at the edge of the tank dome, and then rapidly expand to the centre and outer surface; increasing the amount of reinforcement cannot effectively limit the development of such cracks.